Synthesis and Studies of Co(II), Ni(II) and Cu(II) Complexes with Some Tridentate Schiff Bases - Rai, B.K.; Sharma, Kaushlendra; Singh, A.K. (Asian Journal of Chemistry, 2010)
Complexes of Co(II), Ni(II) and Cu(II) with 3-phenyl-3-(p-aminophenyl)-4-quinazolone semicarbazone (PAPQSC) and 3-phenyl-3-(p-aminophenyl)-4-quinazolone thiosemicarbazone (PAPQTSC) have been synthesized and characterized on the basis of elemental analysis, IR spectra, electronic spectra, magnetic moment data and conductivity measurements. The analytical data of the complexes indicate 1: 2 metal-ligand stoichiometry of the type [M(HL1-2)2] where M = Co(II), Ni(II) and Cu(II). The ligands behaved as binegative tridentate chelating agents and bonded to the metal ion through amine and imine nitrogen and oxygen/sulphur atoms of either semicarbazone or thiosemicarbazone moiety.